Composition of particulate matter during a wildfire smoke episode in an urban area. Issue 6 (21st April 2021) - Sparks, Tamara L.; Wagner, Jeff
Abstract: The composition of wildfire smoke particulate matter (PM) was investigated during a 2018 smoke episode in the San Francisco Bay Area and compared to non-wildfire periods. Scanning electron microscopy (SEM) of passive PM samples deployed at four sites exhibited a higher concentration of submicron, spherical, carbonaceous PM ("tar balls") during the wildfire period compared to the non-wildfire period. Coarse ash aluminosilicates and potassium bearing particles were enhanced as well. Disproportionately more UV light was absorbed by PM during the wildfire period than during the non-wildfire period, indicating a higher organic content consistent with the observed tar balls. An indoor PM sample from a residence operating a medium-efficiency furnace filter during the smoke episode exhibited fine, carbonaceous PM comparable to outdoors, but reduced coarse ash PM. Indoor/outdoor ratios for PM2.5, PM10-2.5, and PM10 were 0.6, 0.1, and 0.5 respectively. SEM of the wildfire furnace filter revealed a greater proportion of tar balls compared to a non-wildfire filter. Relatively rare particles enriched in Cu, Zn, Sn and Pb were observed in wildfire samples, but not in non-wildfire samples. Higher concentrations of Cu, Zn, and Pb during the wildfire were confirmed by inductively coupled plasma mass spectrometry (ICP-MS) of the furnace filter. The use of low-cost passive samplers enabled rapid deployment at multiple locations and indoors and outdoors during the wildfire episode. These measurements suggest smoke impacts were regional in scale and similar across sites, though local variations in PM2.5 magnitudes, particle types, and confounding by local sources were observed. Copyright © 2021 American Association for Aerosol Research